Effect of intermittent subglottic secretion drainage on ventilator-associated pneumonia: A clinical trial - Safdari, Rahimeh (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Secretions contaminated with oral, nasal, and gastric bacteria accumulate in the subglottic space, above the endotracheal tube cuff. If these secretions are aspirated into lower airways, the intubated patient will be susceptible to ventilator-associated pneumonia (VAP). The aim of this study was to investigate the effect of inspiratory pause maneuver for intermittent subglottic secretions drainage (SSD) on the incidence of VAP in patients receiving mechanical ventilation. MATERIALS AND METHODS: This randomized clinical trial was conducted in four intensive care units of educational hospital in Isfahan, Iran. A total of 76 adult patients intubated with a conventional endotracheal tube and connected to ventilators for more than 48 h were selected through convenient sampling and were randomly assigned to undergo intermittent SSD (n = 38) or not (n = 38). In this study, for SSD, we used inspiratory pause/hold key in the ventilators to hyperinflate the lungs. Pressure that produces with this maneuver could remove the secretions from the subglottic space. RESULTS: VAP was found in 10 (26.3%) patients receiving SSD and in 18 (47.4%) patients in the control group (P = 0.04). CONCLUSIONS: SSD using inspiratory pause during mechanical ventilation results in a significant reduction in VAP.